The School of Hawthorne: New England Women Writers after the Civil War - Marek Wilczyński (European Journal of American Studies)
The main argument of the essay is that New England women writers of the late 19th century, such as Mary E. Wilkins Freeman, Alice Brown, Rose Terry Cooke, Annie Trumbull Slosson, and Sarah Orne Jewett, known as post-bellum regional realists, were actually continuing certain elements of Nathaniel Hawthorne’s poetics of fiction. Describing in their short stories and novels New England’s demographic, economic, and cultural decadence, they often used allegory and introduced fantastic elements, which arguably allows to read their works in a way proposed by Walter Benjamin in The Origin of German Tragic Drama.